TANGGAPAN GURU PAUD TENTANG PEMBERIAN REWARD DAN PENGARUHNYA TERHADAP MOTIVASI BELAJAR DAN PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI - Tiara Astari; Siti Nur Aisyah; Diah Andika Sari (JECIES: Journal of Early Childhood Islamic Education Study, 2020)
The purpose of this study was to determine the responses of PAUD teachers in East Ciputat sub-district regarding the effect of reward on learning motivation and socio-emotional development of early childhood. The method used is descriptive quantitative with survey techniques, using a questionnaire (questionnaire) using the google form application. Questionnaires (questionnaires) are given to respondents online via WhatsApp, then the collected data will be analyzed. The study population was kindergarten teachers in East Ciputat District, and the number of respondents was 100 people with the sampling technique using simple random sampling. From the data obtained, as many as 80% of respondents answered that they often gave rewards in the form of good words, namely: good, true, great, cool and smart to children. In addition, as many as 65% of respondents answered that very often they gave an assessment with a thumbs up, clapping and smiling. It is known that the results of the respondent's answer who gave an assessment in the form of a sticker or stamp were 70%. Meanwhile, 72% of respondents answered very often that motivation creates a desire to learn in school children. So motivation which serves as a driving force significantly influences learning attitudes in children. Furthermore, 67% of respondents answered that very often children do learning activities with all their soul and body (willing / not forced, happy, sincere). So based on the theory and the results of the respondents' answers, it can be concluded that motivation is the driving force of the desire to learn in children.